(untitled) (Collaborate Engineering Daily Book Series, 2025)
The development of digital technology, the Internet of Things (IoT), and data analytics have driven a major transformation in the production systems of the manufacturing industry. Companies are required to be able to increase productivity while maintaining product quality to remain competitive in the era of global competition. One effective approach is to design a data-driven production system, which is a system that leverages real-time production data to support fast, accurate, and evidence-based decision-making. This article discusses the concept, design stages, and benefits of implementing a data-based production system in improving operational efficiency and quality control. This system includes the process of collecting data from machines and operators, data processing using analytical software, to visualizing information in the form of dashboard monitoring. The results of the conceptual study show that data-based production systems are able to reduce waste, reduce product defects, shorten lead times, and significantly increase labor productivity. The integration of digital technology and automation is a key factor in realizing an adaptive and sustainable production system.